The Andamans as a "sea of islands": reconnecting old geographies through poaching. Issue 1 (2nd January 2018) - Abraham, Itty
ABSTRACT: The rise of military and political tensions in the Indo-Pacific maritime zone has brought new attention to the Andaman and Nicobar Islands. With this visibility has come a disturbing awareness in some quarters that this Indian archipelago is qualitatively different from the rest of the country. Whether defined in terms of unorthodox cultural practices or the unauthorized presence of other national bodies, the multicultural habitus of the Andamans is deeply unsettling from a geopolitical standpoint that imagines the islands as a natural extension of a homogeneous national-territorial space. This article argues that the persistence of cultural and other heterogeneities in the Andamans should be read as a trace of histories that are intimately tied to the location of this archipelago. Framing the archipelago as a "sea of islands" lying off the littoral of the Andaman Sea rather than as an extension of Indian national space permits unauthorized social relations to become visible again. Once we redraw island geographies, spectral presences begin to appear, taking the form of both foreign bodies as well as narrative contradictions. Currently, these specters are interpellated under the sign of "poaching, " a portmanteau of activities that joins indigenous, settlers, outsiders, and Nature in an illicit assemblage that is presumed to lie outside the law. Contradictions of the poaching discourse should be read as signs of recalcitrance: the complexity of the Andamans that cannot be erased by the violence of denial.